A comparative study of effect of epidermal growth factor on chronic leg ulcers with anti-septic dressing - M., Mallikarjuna Reddy; Sirigireddy, Vijayabhaskarreddy (International Surgery Journal, 2021)
Background: Chronic wounds, particularly non-healing wounds, are one of the most prevalent surgical disorders that a surgeon may see. The characteristic of a chronic wound is that it does not heal despite daily dressings and costly local treatments. Aims of the study to investigate the healing effects of recombinant human epidermal growth factor (hEGF) on non-healing ulcers and to assess the effectiveness, acceptability, and safety of a new epidermal growth factor (EGF) wound dressing. Methods: On 60 patients with chronic non-healing ulcers, a randomized, prospective, and comparative research was conducted in the department of general surgery, SVS medical college and hospital, Mahbubnagar. These 60 patients were separated into two groups, each with fifteen patients. The EGF was applied to group A, whereas normal saline was given to group B. Results: The 60 patients who agreed to participate in the trial were separated into two groups (30 each) that were equal and comparable. Patients who received topical EGF 0.01% gel dressings were assigned to the trial, whereas those who received standard antiseptic wound dressing were assigned to the control group. Six of the fifteen patients in the test group were men, whereas eleven were males and four were females in the control group. When the two groups were compared, the test group had a substantial reduction in ulcer area compared to the control group (p<0.001) Conclusions: EGF is a superior alternative for treating chronic non-healing ulcers because of its cost effectiveness, availability, reduced hospital stay, and simplicity of administration.